Prostate Specific Antigen: The Past, Present and Future - Gill, Harcharan (S. Karger AG, 2013)
AIM: To review current data available on use of prostate specific antigen for screening healthy men for prostate cancer. METHODS: Literature was reviewed and the guidelines from, American cancer Society, American Urologic Association was reviewed. RESULTS: Current screening protocols lead to over diagnosis of prostate cancer. This often results in unnecessary biopsy procedures and treatments. CONCLUSION: We must consider the benefit of screening and treatment with the harms of over diagnosis and over treatment. Newer imaging modalities like magnetic resonance imaging have to be evaluated further.